If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6 = 42 + -5x Reorder the terms: -6 + 7x = 42 + -5x Solving -6 + 7x = 42 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -6 + 7x + 5x = 42 + -5x + 5x Combine like terms: 7x + 5x = 12x -6 + 12x = 42 + -5x + 5x Combine like terms: -5x + 5x = 0 -6 + 12x = 42 + 0 -6 + 12x = 42 Add '6' to each side of the equation. -6 + 6 + 12x = 42 + 6 Combine like terms: -6 + 6 = 0 0 + 12x = 42 + 6 12x = 42 + 6 Combine like terms: 42 + 6 = 48 12x = 48 Divide each side by '12'. x = 4 Simplifying x = 4
| 100a=193748563646564646465646565656 | | 5a-3=5a+4 | | y=-12x-x+20 | | (-5)x(-8)(-9)= | | 6x^2+3=-102 | | 4x+12=-3x+-9 | | 432=36b | | y-84=10.25 | | X-123=77-9x | | 6x+7=8-15 | | (+5)+(+12)+(+17)= | | 9r^2+3=48 | | 436+w=600 | | 70=0.6r | | c^2+12c+36-q^2= | | F(x)x=2.4 | | z+48=136 | | 4x^6+6x^3-7= | | x^2-9+x^2-x=180 | | 4x+12=-3x-9 | | F(x)whenx=2.4 | | -4(8-2m)=-96 | | 4a-3[a-(2a+1)]= | | 2x-85=11x+167 | | x^2-0+45=0 | | A+6a-14=64 | | w^8+17w^4+70= | | 7x+2yz=-3x+1 | | -76-34-16-34= | | 3x-7.6=29.6 | | X+2x+X=90 | | v=20+3u |